Instrumentation of integrally stiffened composite panel with fiber Bragg grating sensors for vibration measurements. (16th July 2015) - Oman, Kyle; Hoe, Bram Van; Aly, Karim; Peters, Kara; Steenberge, Geert Van; Stan, Nikola; Schultz, Stephen
Abstract: We evaluate the performance of fiber Bragg grating (FBG) sensors for the measurement of dynamic strains in complex composite structures. The particular structure used in this study is an integrally stiffened composite panel for which the stiffeners and skin are fabricated in a single layup and cure process. Surface-mounted FBG sensors are bonded to the panels after curing, whereas embedded FBG sensors are successfully incorporated during the fabrication process. A finite element model was also constructed of the stiffened panel. The panels were subjected to repeated impacts and the post-impact vibration response of the panel was measured through the FBG sensor responses. Little change to the global response of the panel was observed after the repeated impacts, through the dynamic response of the surface-mounted FBGs. Pulsed phase thermography and micro-computer-tomography imaging of the panel confirmed that the damage was localized near the impact locations, producing negligible changes to the global response of the panel. All of the embedded FBG sensors survived the fabrication and multiple impacts; however, as these were embedded close to the neutral axis of the panel, they were not very sensitive to the vibration modes. Excitation of the panel near the first natural frequency did produce a measurable response in the FBG sensors, confirming their functionality.